167k views
0 votes
HELP MEE PLZZZZ I DON'T UNDERSTAND THIS

HELP MEE PLZZZZ I DON'T UNDERSTAND THIS-example-1
User Evolve
by
5.3k points

1 Answer

3 votes

Answer: Choice D.
6.44 * 10^(-4)

========================================================

Work Shown:

We multiply the coefficients 9.2 and 7 to get 64.4, which is the same as 6.44*10^1 in scientific notation. When multiplying exponential expressions with the same base, we add the exponents

This is what the steps could look like


\left(9.2 * 10^(-9)\right)*\left(7 * 10^(4)\right)\\\\\left(9.2*7\right)*\left(10^(-9) * 10^(4)\right)\\\\\left(64.4\right)*\left(10^(-9+4)\right)\\\\\left(6.44* 10^(1)\right)*\left(10^(-5)\right)\\\\6.44*\left(10^(1)* 10^(-5)\right)\\\\6.44*\left(10^(1+(-5))\right)\\\\6.44* 10^(-4)\\\\

The final result is in scientific notation as the coefficient c is restricted such that
0 \le c < 10

User Sir Neuman
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.